(untitled) (Annals of Medical Research, 2025)
Aim: The most common liver disease in children is metabolic dysfunction-associated steatotic liver disease. We expect increased diaphragm thickness in pediatric patients with hepatosteatosis. We aimed to compare diaphragm thickness in children with hepatosteatosis with that in the control group and to discuss the results in light of the current literature. Materials and Methods: The study included 56 patients with metabolic dysfunction-associated steatotic liver disease and 78 healthy controls. The diaphragm measurement of the patient and control groups was performed from the anterior caudal part of the diaphragm at the end of expiration from the right and left sides. Results: Diaphragm thickness, BMI, weight, and height Z scores were significantly greater in the group with fatty liver. We found a significant positive correlation between the stages of fatty liver and anthropometric measurement Z score values ​​with diaphragm thickness. Conclusion: The current study found that diaphragm thickness was thicker in pediatric patients with hepatosteatosis than that in healthy individuals and was positively correlated with anthropometric measurements. However, further studies are needed to evaluate diaphragmatic muscle function.